2016
DOI: 10.1002/hyp.10814
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of impacts of climate change and human activities on streamflow in the Poyang Lake basin, China

Abstract: Abstract:Variations in streamflows of five tributaries of the Poyang Lake basin, China, because of the influence of human activities and climate change were evaluated using the Australia Water Balance Model and multivariate regression. Results indicated that multiple regression models were appropriate with precipitation, potential evapotranspiration of the current month, and precipitation of the last month as explanatory variables. The NASH coefficient for the Australia Water Balance Model was larger than 0.84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(51 citation statements)
references
References 31 publications
3
48
0
Order By: Relevance
“…Zhang et al found that human-induced and climate-induced influences on streamflows are different in the five Poyang Lake sub-basins. Climate change is the major driving factor for the streamflow increases within the Ganjiang, Xinjiang, and Raohe River basins; however, anthropogenic activities are the principal driving factors for the streamflow increase of the Xiushui River basin and for the streamflow decrease of the Fuhe River basin [32].…”
Section: Discussion On Temporal Changes In Streamflow and Water Levelmentioning
confidence: 99%
“…Zhang et al found that human-induced and climate-induced influences on streamflows are different in the five Poyang Lake sub-basins. Climate change is the major driving factor for the streamflow increases within the Ganjiang, Xinjiang, and Raohe River basins; however, anthropogenic activities are the principal driving factors for the streamflow increase of the Xiushui River basin and for the streamflow decrease of the Fuhe River basin [32].…”
Section: Discussion On Temporal Changes In Streamflow and Water Levelmentioning
confidence: 99%
“…Zhang, Fu, et al () found that the average streamflow in the Hexi Corridor of Northwest China would increase by 10.5 to 22.0% during 2021 to 2050. Similarly, a 12.8% increase in streamflow was projected during 2021 to 2050 in the Heihe catchment (Zhang, Liu, Yin, et al, ). Most of these works are disjointed as they are aimed at a particular region or an individual river basin (Li et al, ; Li, Zhang, Xu, et al, ; Zhang, Fu, et al, ; Zhang, Liu, Singh, et al, ).…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, reliable and accurate precipitation information at sufficient spatial and temporal resolution is essential not only for the study of climate trends, but also for water resource management [2]. Traditionally, hydrologic simulations are usually based on historical gauge observations that may not models in Australia [27], but, nowadays, it is being used worldwide [28,29], for both humid and dry basins. The Thornthwaite and Mather water balance model has been successfully used in different water balance research studies in Spain [30].…”
Section: Introductionmentioning
confidence: 99%